A convenient synthesis of dialkyl 2-(2-haloethylidene)malonates, cyanoacetates and halocrotonates by one carbon extension. Issue 26 (24th June 2015) - Sathishkumar, S.; Mahasampathgowri, S.; Balasubramanian, K.K.; Saiganesh, R.
Graphical abstract: Abstract: 2-Haloethylidenemalonates are highly reactive species and useful synthons for the synthesis of Famvir®, an antiviral drug. Simple methods for the preparation of 2-haloalkylidenemalonates are not available. We have developed a novel and non-cumbersome methodology for the synthesis of dialkyl 2-(2-haloethylidene)malonates, cyanoacetates and halocrotonates by one carbon extension of dialkyl (2-alkoxymethylene)malonates, cyanoacetates and 3-alkoxyacrylates with dimethylsulfoxonium methylide.